ANALYSIS OF A SAMPLE APPLICATION FOR WHOLE TREE EXTRACTION USING SkylineXL 24.1: A CASE STUDY FROM KAHRAMANMARAS, TURKIYE - Gülcı, Neşe; Sessions, John; Gülci, Sercan; Akay, Abdullah Emin (My University, 2025)
In mountainous areas, timber extraction operations are commonly carried out using skylines. Transporting forest products with a skyline is an efficient method commonly used in mountainous areas with challenging terrain conditions and in areas where environmental factors are crucial. There are four main types of cable systems: Highlead, Standing, Running, and Live Skyline. Because of reduced lift, Highlead is not a skyline system, but rather a method suitable for shorter yarder distances at steep terrain. Standing, Running, and Live Skylines are cable logging systems that have a suspended cable used for suspending and yarding products. The installation stages of these skylines require expertise and need to be carefully planned. The payload and cable tensions are very important factors for preventing work accidents and ensuring efficient cable logging operations. There are various software programs developed for analyzing skyline systems. This study aimed to analyze a sample logging application using one of the well-known software, SkylineXL 24.1. The study was implemented in the KSU Başkonuş Research and Application Forest in Kahramanmaras, Turkiye. According to the results for the standing system, the minimum required skyline length was 540 m, while the Koller yarder capacity was 579 m. The maximum allowable tension of the skyline (10.584 kg) has been reached at each terrain point in this study.
Keywords: Forestry operations; skyline systems; payload; cable tension; SkylineXL